Urban pollution in the Danube and Western Balkans regions: The impact of major PM2.5 sources. (December 2019) - Belis, Claudio A.; Pisoni, Enrico; Degraeuwe, Bart; Peduzzi, Emanuela; Thunis, Philippe; Monforti-Ferrario, Fabio; Guizzardi, Diego
Abstract: The SHERPA tool was used to assess the major pollution sources and the geographical areas impacting on the PM2.5 of the main cities in the Danube and Western Balkans regions. The activity sectors influencing most the PM2.5 levels in the study area are energy production (22%), agriculture (19%), residential combustion (16%) and road transport (7%). The energy production in inefficient coal-fuelled power plants was identified as one of main source of PM2.5 in the Western Balkans. As for the geographical origin of PM2.5, the transboundary pollution is confirmed as the main origin of PM2.5 (44%) in the investigated cities, while the city own emissions and the national sources outside the concerned city impact on average 22% and 15%, respectively. An association was observed between the long-range transport and the impact of agriculture and energy production, while both local urban emissions and long-range transport were associated with the residential sector. A special attention is given in this study to biomass, a renewable source, which use is often promoted in the frame of climate and energy policies. Nevertheless, the combustion of biomass in inefficient small appliances has considerable particulate matter emissions and therefore this type of practice impacts negatively on air quality. Considering that biomass is traditionally used in South-East Europe as fuel for residential heating, the interpretation of the model results was supported with the estimation of biomass burning contributions to PM2.5 obtained with receptor models and data on biomass fuel consumption from the literature. The analysis of the contributions from biomass burning derived from receptor models suggests that biomass burning is the dominant source within the residential heating sector in the studied area and that the emissions from this source are likely underestimated. This study concludes that more effort is needed to improve the estimations of biomass burning emissions and that policies to improve air quality in the cities should involve a geographic context wider than the city level. Highlights: The SHERPA tool based on EMEP model and emissions was used for source quantification The residential sector impact was compared with biomass burning receptor model data Coal-fuelled power plants are among the main sources of PM2.5 in the Western Balkans Biomass burning is the dominant source within the residential heating sector Transboundary pollution is associated with agriculture and energy sectors